Risk factors associated with death among influenza A (H1N1) patients, Tamil Nadu, India, 2010 - Balaganesakumar, S; Murhekar, M; Swamy, K; Kumar, M; Manickam, P; Pandian, PRT (Journal of postgraduate medicine, 2013)
Background: Limited information is available about the risk factors associated with death among patients of influenza A (H1N1) in India. Aims: To describe the epidemiology of laboratory-confirmed influenza A (H1N1) patients and identify risk factors associated with death. Settings and Design: We reviewed the surveillance data of laboratory-confirmed patients in Tamil Nadu, India, for the year 2010. We conducted a case-control study by comparing 70 laboratory-confirmed A (H1N1) patients who died (cases) with 210 A (H1N1) patients who recovered (controls) to identify the risk factors for deaths. Materials and Methods: We interviewed the controls and immediate care-takers of the influenza patients who died to collect information about socio-demographic details and co-morbid conditions. We used an abstraction form to collect the information about the clinical details from the case records of the hospitals where the cases and controls received treatment. Statistical Analysis: We analysed the surveillance data by time, place and person. We conducted univariate and multivariate logistic regression analysis for identifying factors associated death. Results: During 2010, 1302 laboratory-confirmed cases were reported to the Tamil Nadu surveillance unit. Of these, 72 patients died (case fatality=5.5%). About 2/3 of the cases and 40% of the deaths were from three districts. On multivariate analysis, past history of diabetes, treatment in private hospitals, treatment with corticosteroids during illness, visit to >1 healthcare facility before laboratory confirmation and delay of >48 h in starting antivirals were found to be independently associated with the deaths. Conclusions: Influenza patients with previous history of diabetes, who had treatment with corticosteroids during illness, and started with antivirals after 48 h of onset of symptoms, were at higher risk of adverse outcome. In order to reduce the risk of death during future waves of influenza in Tamil Nadu, the physicians need to be sensitised regarding (1) higher risk of adverse outcomes among A (H1N1) patients with diabetes; (2) adherence to the national protocol for categorisation of cases; (3) prompt initiation of antivirals for severe cases; and (4) avoidance of systemic corticosteroids during management.